Pelatihan Promosi Digital & Foto Produk Menggunakan Smartphone Bagi Tim Kreatif Pojok UMKM Desa Nagasepaha - Aan Darmawan, I Gusti Ngurah; Pramiswara, I Gusti Agung Ngurah Agung Yudha; Wasisto, Roni Han (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Business actors of micro, small, and medium enterprises (MSME) may use Internet resources to increase sales of their products and services. Internet users, especially social media are growing every year and becoming the targets in promoting digital-based MSME products. For this reason, MSME actors must have insight into digital promotion, including having expertise in creating good and attractive product photos. Good and attractive product photos are one of the keys to attracting potential customers. Nagasepaha Village is one of the villages in Buleleng sub-district, Buleleng regency, Bali Province which has MSME with cultural products such as glass puppet paintings, jewelry and saab (Hindus ceremonial stuff from palm leaves) handicrafts. In order to improve product marketing, a creative team named MSME Corner of Nagasepaha Village was formed to carry out digital-based promotions. The members of the MSME Corner of Nagasepaha Village creative team are young people who are used to using smartphones and their camera features. However, based on the results of the interviews, they did not gain any knowledge about digital promotion and photography techniques using smartphones and supporting equipment in the form of mini photo studio boxes. Therefore, to meet this need, training on digital promotion and photography techniques is carried out in the form of Community Service, both with a workshop of material and hands-on practice. The results of the evaluation carried out were an increase in the skills of the participants to produce good and attractive product photos through photographic techniques and the use of supporting tools such as a mini photo studio box.